PENGARUH KARAKTERISTIK INDIVIDUAL DAN KARAKTERISTIK PEKERJAAN TERHADAP KOMITMEN ORGANISASIONAL PADA PEGAWAI KANTOR BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA (BKPSDM) SUMBAWA BESAR - Maharani, Miranda; Sarifudin Serip (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the influence of: (1) Individual Characteristics on Organizational Commitment, and (2) Job Characteristics on Organizational Commitment among employees of the Sumbawa Besar Civil Service and Human Resources Development Agency (BKPSDM). This study is a causal associative study with a quantitative approach, using a questionnaire as the primary data collection technique. The population in this study was all 47 employees of the Sumbawa Besar BKPSDM, using a census or saturated sampling method. The data analysis tool used was multiple linear regression analysis with the assistance of the SPSS program. The results of the study indicate that: (1) Individual Characteristics have a positive and significant effect on Organizational Commitment. (2) Job Characteristics have a positive and significant effect on Organizational Commitment among employees of the Sumbawa Besar BKPSDM.